2019
DOI: 10.1038/s41598-019-56759-3
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of factors for decreased lung function in elderly patients with type 2 diabetes

Abstract: Chronic obstructive pulmonary disease (COPD) often accompanies type 2 diabetes mellitus (T2DM). However, background factors affecting these diseases in the elderly remain unclear. Eligible patients with T2DM were divided into two age groups—non-elderly (<65 years) and elderly (≥65 years); COPD, ratio of forced expiratory volume in one second to forced expiratory volume (FEV1/FVC ratio), and percent predicted forced expiratory volume in one second (FEV1% predicted) were examined, and factors related to reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Evaluation of the nutrition status with BMI was essential in prognosis of other pulmonary disease patients including the chronic obstructive pulmonary disease and the nosocomial infection. (26)(27)(28)(29) The present study suggested that the gender of females might be risk for the prolonged hospitalization. The reason why the hospitalization stay tended to be long in the aged females pneumonia patients was not clear, (30) as the number of the patients with good performance status (0 + 1) was not different between males (14 cases) and females (13 cases) and there was no significance difference between the genders regarding the other factors evaluated in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…Evaluation of the nutrition status with BMI was essential in prognosis of other pulmonary disease patients including the chronic obstructive pulmonary disease and the nosocomial infection. (26)(27)(28)(29) The present study suggested that the gender of females might be risk for the prolonged hospitalization. The reason why the hospitalization stay tended to be long in the aged females pneumonia patients was not clear, (30) as the number of the patients with good performance status (0 + 1) was not different between males (14 cases) and females (13 cases) and there was no significance difference between the genders regarding the other factors evaluated in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, there is evidence that the concentrations of insulin, C-peptide, leptin and the glucose/insulin ratio are associated with recurrent wheezing in preschool children [ 36 ]. A number of studies indicate an increase in the level of C-peptide in patients with COPD [ 37 , 38 , 39 ]. At the same time, none of the studies evaluated the level of C-peptide and insulin in individuals with combined pathology of AO and bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although pulmonary and renal diseases were considered as 12.4% associated with DM in elderly patients suggested that albuminuria and low glomerular filtration rate are associated with frontal lobe dysfunction in elderly type 2 diabetic patients [23]. Moreover in the elderly, male sex, diabetes, insulin therapy and high C-peptide immune reactivity levels were considered as risk factors [24]. Saudi patients were the most prevalence with 2061 patients (72.2%) compared with Arabic Middle East with 461 patients (16.2%) and other nationalities with (11.6%).…”
Section: Discussionmentioning
confidence: 99%